Reception Of English Law Under Sections 3 & 5 Of The Civil Law Act 1956 (Revised 1972) - Chia, Joseph (Journal of Malaysian and Comparative Law, 1974)
(1974) 1 (1) JMCL 3 Reception Of English Law Under Sections 3 & 5 Of The Civil Law Act 1956 (Revised 1972) – Joseph Chia